Peripheral vascular access for therapeutic plasma exchange: A practical approach to increased utilization and selecting the most appropriate vascular access. Issue 3 (19th March 2020) - Barth, David; Sanchez, Amber; Thomsen, Anna‐Marie; Garcia, Alicia; Malachowski, Roman; Weldon, Rebecca; Mayhew, Michaela; Mudie, Kari; Faller, Dawn; Schwartz, Joseph
Abstract: Background: Therapeutic plasma exchange (TPE) is used in the treatment of many diseases. At present, peripheral vascular access (PVA) is an underutilized method of vascular access in TPE. It should be considered more frequently due its relatively low risk for adverse events, particularly infections. Methods: The Advancing Vascular Access in Apheresis Working Group met in December 2017 for an extensive review and discussion of vascular access for TPE and developed a "road map" providing detailed information regarding clinical situations in which PVA‐based TPE would and would not be appropriate. Results: The road map is consistent with current recommendations that PVA should be used in combination with TPE whenever possible. PVA should be considered for patients who do not have existing central lines and who are stable. The patient should have peripheral veins that will allow for adequate treatment and must be able to comply with the process of achieving and maintaining peripheral access. There should be expert clinical assessment of veins, and this evaluation may include ultrasound and/or near infrared evaluation. Conditions that would prompt a switch from PVA to an alternate method of venous access include loss of venous access, patient preference, or development of a requirement for very frequent treatment over a long period of time. Conclusions: While PVA is not suitable for all patients requiring TPE, it has significant safety advantages over other approaches and should be employed whenever possible.